Release Coating Composition

The curable release coating composition with aliphatic unsaturated polyorganosiloxane and silica-treated particles addresses blocking and cloudiness issues, providing transparent and anti-blocking release coatings for electronic devices.

JP2025500220AActive Publication Date: 2025-01-09DOW SILICONES CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024535698
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2021-12-21
Publication Date
2025-01-09
Estimated Expiration
2041-12-21

AI Technical Summary

Technical Problem

Conventional silicone release coatings suffer from blocking issues when rolled up, leading to adjacent layers sticking together, and they often appear cloudy, limiting their use in transparent applications, especially in electronic devices.

Method used

A curable release coating composition comprising aliphatic unsaturated polyorganosiloxane, a crosslinking agent, hydrosilylation reaction catalyst, and silica-treated particles, which are applied and cured to form a release liner with low peel forces and transparent appearance, preventing blocking.

Benefits of technology

The composition achieves low peel forces, transparency, and anti-blocking properties, making it suitable for electronic device applications such as touch panels and adhesive transfer films.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025500220000001_ABST
    Figure 2025500220000001_ABST
Patent Text Reader

Abstract

The curable release coating composition comprises: (A) an aliphatically unsaturated polyorganosiloxane having two or more alkenyl groups per molecule; (B) a crosslinker having two or more silicon-bonded hydrogen atoms per molecule in an amount sufficient to provide a molar ratio of silicon-bonded hydrogen atoms to alkenyl groups in the curable release coating composition of from 0.8:1 to 5:1; (C) a catalytic amount of a hydrosilylation reaction catalyst; and (D) from 0.01% to 5% by weight, based on the weight of the curable release coating composition excluding solvent, if present, of particles of the cured organosiloxane composition, optionally having a silica treated coating, having an average particle size of from 0.5 to 30 micrometers.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a curable release coating composition and release liners prepared by applying the release coating composition to a substrate, such as a plastic film or paper, and curing the release coating composition by the application of heat. [Background technology]

[0002] (Introduction) Silicone release coatings are useful in applications where a relatively non-adhesive surface is required. Single-sided liners, such as the backing paper or film of pressure-sensitive adhesive labels, are usually adapted to temporarily hold the label without affecting the adhesive properties of the label. Double-sided liners, such as interleaving papers or films for double-sided and transfer tapes, are used to protect the adhesive tape. These liners are generally manufactured in long sheets and then rolled up for ease of transportation and storage. Conventional silicone release coating compositions can achieve ultra-low release forces (e.g., <5.0 grams per inch) for adhesives, typically at coat weights of >1.0 grams per square meter, but suffer from blocking problems in which adjacent layers often stick together between successive liner rolls during storage. The incorporation of silica particles into silicone release coating compositions can prevent blocking when coating on a substrate, but often makes the resulting release coating appear hazy, which limits the use of silicone release coatings for tape release, label release, and adhesive transfer films. In particular, many electronic device applications require transparent release coatings. It is desirable for the release coating to have anti-blocking properties to increase production efficiency and avoid potential coating damage when separating two coated surfaces that are laminated or placed in contact with each other during storage, packaging and / or shipping of the resulting release liner that is wound up into large rolls.

[0003] There remains a need to identify release coating compositions that can provide release coatings having the above-mentioned low release forces with clear appearance and anti-blocking properties while maintaining other properties, including subsequent adhesive strength. Summary of the Invention

[0004] The present invention provides a curable release coating composition that can be cured into a cured release coating with low release force to adhesives with clear appearance and antiblocking properties. The release coating composition of the present invention comprises a novel combination of an aliphatically unsaturated polyorganosiloxane, a crosslinker, and a hydrosilylation reaction catalyst, a specific amount of particles of a cured organosiloxane composition, and an optional silica-treated coating. The release coating composition can be coated on at least one surface of a substrate and cured by hydrosilylation reaction to prepare a release liner.

[0005] In a first aspect, the present invention provides a curable release coating composition comprising: (A) an aliphatic unsaturated polyorganosiloxane having two or more alkenyl groups per molecule; (B) a crosslinker having two or more silicon-bonded hydrogen atoms per molecule in an amount sufficient to provide a molar ratio of silicon-bonded hydrogen atoms to alkenyl groups in the curable release coating composition of from 0.8:1 to 5:1; (C) a catalytic amount of a hydrosilylation reaction catalyst; (D) 0.01% to 5% by weight, based on the weight of the curable release coating composition excluding solvent, if present, of particles of a cured organosiloxane composition, optionally having a silica treated coating, having an average particle size of 0.5 to 30 micrometers; The present invention relates to a curable release coating composition comprising:

[0006] In a second aspect, the present invention provides a method for preparing a release liner comprising a release coating on at least one surface of a substrate, the method comprising the steps of: Optionally, treating at least one surface of the substrate; 1) applying a curable release coating composition of the first aspect to a surface of a substrate, and optionally, 2) removing the solvent, if present; 3) curing the composition to form a release coating on the surface of the substrate; and The method includes:

[0007] In a third aspect, the invention is a release liner comprising a substrate and a release coating present on at least one surface of the substrate, the release coating being formed by curing the curable release coating composition of the first aspect. [Brief description of the drawings]

[0008] [Figure 1] 1 shows a partial cross-sectional view of a release liner 100. The release liner comprises a release coating 101 prepared by curing a curable release composition of the present invention on a first surface 102 of a film substrate 103. The release liner 100 further comprises a support 104 disposed on an opposing surface 105 of the film substrate 103. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Test methods refer to the test method most recent at the priority date of this document unless a date is given with the test method number. Reference to a test method includes both a reference to the testing society and the test method number. The following test method abbreviations and identifiers apply herein: ASTM refers to ASTM International methods.

[0010] Products identified by trade names refer to compositions available under those trade names as of the priority date of this document.

[0011] "And / or" means "and, or alternatively." All ranges are inclusive of the endpoints unless otherwise indicated.

[0012] The "viscosity" of the polysiloxane is measured at 25 degrees Celsius (° C.) using a Brookfield DV2T viscometer equipped with spindle LV1.

[0013] standard 1 H, 13 C, and 29 The chemical structure of the polysiloxane is determined by Si nuclear magnetic resonance (NMR) analysis.

[0014] As used herein, "alkyl" refers to a cyclic, branched or unbranched saturated monovalent hydrocarbon group. Examples of alkyl groups include methyl, ethyl, propyl (e.g., isopropyl and / or n-propyl), butyl (e.g., isobutyl, n-butyl, tert-butyl, and / or sec-butyl), pentyl (e.g., isopentyl, neopentyl, and / or tert-pentyl), hexyl, heptyl, octyl, nonyl, decyl, branched alkyl groups of 6 or more carbon atoms, and cyclic alkyl groups such as cyclopentyl and cyclohexyl.

[0015] As used herein, "aryl" refers to a cyclic, fully unsaturated hydrocarbon group. Aryl is exemplified by, but not limited to, cyclopentadienyl, phenyl, anthracenyl, and naphthyl. Monocyclic aryl groups may have 5 to 9 carbon atoms, 6 to 7 carbon atoms, or 5 to 6 carbon atoms. Polycyclic aryl groups may have 10 to 17 carbon atoms, 10 to 14 carbon atoms, or 12 to 14 carbon atoms.

[0016] As used herein, "aralkyl" refers to an alkyl group having a pendant and / or terminal aryl group, or an aryl group having a pendant alkyl group. Exemplary aralkyl groups include tolyl, xylyl, benzyl, phenylethyl, phenylpropyl, and phenylbutyl.

[0017] As used herein, "alkenyl" refers to a branched or unbranched monovalent hydrocarbon group having one or more carbon-carbon double bonds.

[0018] The curable release coating composition of the present invention comprises (A) one or more aliphatically unsaturated polyorganosiloxanes having two or more alkenyl groups per molecule. The aliphatically unsaturated polyorganosiloxane (A) can be selected from (A-1) Q-branched polyorganosiloxanes, (A-2) silsesquioxanes, (A-3) linear polyorganosiloxanes, or combinations of two or more of (A-1), (A-2), and (A-3).

[0019] The Q branched polyorganosiloxanes (A-1) useful in the present invention have the unit formula (AI): (R 1 3SiO 1 / 2 ) a (R 2 R 1 2SiO 1 / 2 ) b (R 1 2SiO 2 / 2 ) c (R 2 R 1 SiO 2 / 2 ) c’ (SiO 4 / 2 ) d (AI), wherein each R 1 are independently a monovalent hydrocarbon group free of aliphatic unsaturation or a monovalent halogenated hydrocarbon group free of aliphatic unsaturation, and each R 2 are independently an alkenyl group, subscript a≧0, subscript b>0, 995≧c+c′≧15, and subscript d>0.

[0020] R 1 The monovalent hydrocarbon groups of R are exemplified by alkyl groups of 1 to 6 carbon atoms, aryl groups of 6 to 10 carbon atoms, halogenated alkyl groups of 1 to 6 carbon atoms, or halogenated aryl groups of 6 to 10 carbon atoms. 1Suitable alkyl groups for R may include, for example, methyl, ethyl, propyl (e.g., iso-propyl and / or n-propyl), butyl (e.g., isobutyl, n-butyl, tert-butyl, and / or sec-butyl), pentyl (e.g., isopentyl, neopentyl, and / or tert-pentyl), hexyl, and branched saturated hydrocarbon groups of 6 carbon atoms. 1 Examples of suitable aryl groups for R are exemplified by phenyl, tolyl, xylyl, naphthyl, benzyl, and dimethylphenyl. 1 Suitable halogenated alkyl groups for are exemplified by the above-mentioned alkyl groups in which one or more hydrogen atoms are replaced with halogen atoms such as F or Cl, but are not limited thereto. For example, fluoromethyl, 2-fluoropropyl, 3,3,3-trifluoropropyl, 4,4,4-trifluorobutyl, 4,4,4,3,3-pentafluorobutyl, 5,5,5,4,4,3,3-heptafluoropentyl, 6,6,6,5,5,4,4,3,3-nonafluorohexyl, and 8,8,8,7,7-pentafluorooctyl, 2,2-difluorocyclopropyl, 2,3-difluorocyclobutyl, 3,4-difluorocyclohexyl, and 3,4-difluoro-5-methylcycloheptyl, chloromethyl, chloropropyl, 2-dichlorocyclopropyl, and 2,3-dichlorocyclopentyl are examples of suitable halogenated alkyl groups. 1 Suitable halogenated aryl groups for are exemplified, but not limited to, the aryl groups described above in which one or more hydrogen atoms have been replaced with a halogen atom, such as F or Cl. For example, chlorobenzyl and fluorobenzyl are suitable halogenated aryl groups. 1 may be the same or different. 1 can be an alkyl group. Desirably, each R 1 is independently methyl, ethyl, or propyl, and more preferably each R 1 is methyl.

[0021] R 2 The alkenyl group of R is capable of hydrosilylation. 2The alkenyl group represented by R typically has 2 to 8 carbon atoms, 2 to 6 carbon atoms, or 2 to 4 carbon atoms. 2 Suitable alkenyl groups for each R are exemplified by vinyl, allyl, butenyl, hexenyl, and the like. 2 may be the same or different. Desirably, each R 2 is selected from vinyl or hexenyl. 2 can be a vinyl group.

[0022] In the unit formula (AI), the subscript a can be 0 or more (≧0), generally 22 or less, and 20 or less, 15 or less, 10 or less, or even 5 or less. The subscript b can be greater than 0 (>0), >1, or 2 or more, 3 or more, or even 4 or more, and generally 22 or less, and 20 or less, 15 or less, or even 10 or less. The subscript c can range from 15 to 995, and can be 15 or more, 50 or more, or even 100 or more, and generally 995 or less, and 800 or less, or even 400 or less. The subscript c′ can be 0 or more, 1 or more, 5 or more, or even 10 or more, and generally 995 or less, and 800 or less, or even 400 or less. Subscript d can be greater than 0 (>0) and equal to or greater than 1, while at the same time generally being equal to or less than 10, equal to or less than 5, or even equal to or less than 1. Desirably, subscript d is 1 or 2. When subscript d=1, subscript a can be 0 and subscript b can be 4.

[0023] The subscripts in the above formula (AI) may have a value sufficient to provide a vinyl content of the Q branched polyorganosiloxane (A-1) of 0.1% or more, and may be 0.15% or more, or even 0.2% or more, while generally being 5.0% or less, 2.0% or less, 1.5% or less, 1.0% or less, or even 0.8% or less, by weight, based on the weight of the Q branched polyorganosiloxane (A-1).

[0024] Q The branched polyorganosiloxane (A-1) has at least two groups of the formula (R 1 2SiO2 / 2 ) y where each subscript y in the formula is independently 2 to 100. Alternatively, the branched siloxane may comprise four polydiorganosiloxane chains of the formula (R 1 2SiO 2 / 2 ) z The polydiorganosiloxane chain is bonded to the formula (SiO 4 / 2 ) units, where each subscript z in the formula is independently 1 to 100.

[0025] Q branched polyorganosiloxane (A-1) can be one Q branched polyorganosiloxane or a combination of two or more Q branched polyorganosiloxanes of formula (AI), which can differ in one or more properties selected from molecular weight, structure, siloxane unit and sequence. Suitable Q branched polyorganosiloxanes can include those disclosed in U.S. Patent No. 6,806,339.

[0026] The silsesquioxanes (A-2) useful in the present invention have the unit formula (A-II): (R 1 3SiO 1 / 2 ) e (R 2 R 1 2SiO 1 / 2 ) f (R 1 2SiO 2 / 2 ) g (R 1 SiO 3 / 2 ) h (A-II), wherein R 1 and R 2 is as defined above in formula (AI), subscript e≧0, subscript f>0, subscript g is from 15 to 995, and subscript h>0. 1 is methyl. Preferably, R 2 is vinyl.

[0027] The subscript e can be 0 or more, 1 or more, 2 or more, or even 3 or more, and at the same time generally 12 or less, 10 or less, 7 or less, 5 or less, or even 3 or less. The subscript f can be greater than 0 (>0), 1 or more, or more than 1, and at the same time generally 12 or less, 10 or less, 7 or less, 5 or less, 3 or less, or even 2 or less. The subscript g can be 15 or more, 20 or more, 50 or more, or even 100 or more, and at the same time generally 995 or less, 800 or less, 400 or less, or even 200 or less. The subscript h can be greater than 0 (>0), 1 or more, or even 2 or more, and at the same time generally 10 or less, 8 or less, 5 or less, 2 or less, or even 1 or less. If the subscript h=1, the subscript f can be 3 and the subscript e can be 0.

[0028] The value of subscript f may be sufficient to provide a silsesquioxane of formula (A-II) having an alkenyl content of 0.1% or more, and may be 0.15% or more, 0.2% or more, or even 0.24% or more, by weight, based on the weight of silsesquioxane (A-2), while generally being 1% or less, 0.8% or less, or even 0.6% or less.

[0029] The silsesquioxane may be one silsesquioxane or a combination of two or more silsesquioxanes of formula (A-II), which may differ in one or more properties selected from molecular weight, structure, siloxane unit and sequence. Suitable silsesquioxanes (A-2) may include those disclosed in U.S. Pat. No. 4,374,967.

[0030] The linear polydiorganosiloxanes (A-3) useful in the present invention may have alkenyl groups which may be located at terminal positions, pendant positions, or both terminal and pendant positions. Desirably, the polydiorganosiloxanes have an average of one or more terminal alkenyl groups per molecule. The polydiorganosiloxanes (A-3) may be selected from the group consisting of (A-III-1), (A-III-2), or combinations thereof: (R 1 2R2 SiO 1 / 2 )2(R 1 2SiO) n (R 1 R 2 SiO) o (A-III-1), (R 1 3SiO 1 / 2 )2(R 1 2SiO) p (R 1 R 2 SiO) q (A-III-2), wherein R 1 and R 2 is set forth above in formula (AI), wherein subscript n is from 5 to 10,000 and subscript o has a value sufficient to provide an alkenyl content, by weight, of from 0.01% to 5.0%, from 0.05% to 2.0%, from 0.10% to 1.5%, from 0.2% to 1.0%, based on the weight of the polydiorganosiloxane of formula (A-III-1). The subscript p is 5 to 10,000, and the subscript q is sufficient to provide an alkenyl content, by weight, based on the weight of the polydiorganosiloxane of formula (A-III-2), of 0.01% to 5.0%, which can be 0.01% or more, 0.05% or more, 0.10% or more, or even 0.2% or more, while generally being 5.0% or less, and 2.0% or less, 1.5% or less, or even 1.0% or less.

[0031] The polydiorganosiloxane (A-3) may comprise one polydiorganosiloxane or a combination of two or more polydiorganosiloxanes that may differ in one or more properties selected from molecular weight, structure, siloxane units, and sequence. The polydiorganosiloxane (A-3) may comprise any one or any combination of two or more of the following polydiorganosiloxanes: i) dimethylvinylsiloxy-terminated polydimethylsiloxane, ii) dimethylvinylsiloxy-terminated poly(dimethylsiloxane / methylvinylsiloxane); iii) dimethylvinylsiloxy-terminated polymethylvinylsiloxane; iv) trimethylsiloxy-terminated poly(dimethylsiloxane / methylvinylsiloxane); v) trimethylsiloxy-terminated polymethylvinylsiloxane; vi) dimethylvinylsiloxy-terminated poly(dimethylsiloxane / methylvinylsiloxane); vii) dimethylvinylsiloxy-terminated poly(dimethylsiloxane / methylphenylsiloxane); viii) dimethylvinylsiloxy-terminated poly(dimethylsiloxane / diphenylsiloxane); ix) phenyl, methyl, vinyl-siloxy terminated polydimethylsiloxanes; x) dimethylhexenylsiloxy-terminated polydimethylsiloxane, xi) dimethylhexenylsiloxy-terminated poly(dimethylsiloxane / methylhexenylsiloxane); xii) dimethylhexenylsiloxy-terminated polymethylhexenylsiloxane, xiii) trimethylsiloxy-terminated poly(dimethylsiloxane / methylhexenylsiloxane); xiv) trimethylsiloxy-terminated polymethylhexenyl siloxanes; xv) dimethylhexenylsiloxy-terminated poly(dimethylsiloxane / methylhexenylsiloxane), and xvi) Dimethylvinylsiloxy terminated poly(dimethylsiloxane / methylhexenylsiloxane).

[0032] The curable release coating composition of the present invention also includes (B) one or more crosslinkers (also referred to as "SiH crosslinkers") having 2 or more, or even 3 or more silicon-bonded hydrogen (SiH) atoms per molecule. The SiH crosslinkers may have a concentration of hydrogen atoms (H) as SiH (i.e., concentration of silicon-bonded hydrogen atoms) of 0.1% or more, and may be 0.2% or more, 0.3% or more, 0.4% or more, 0.5% or more, 0.6% or more, 0.7% or more, 0.8% or more, or even 0.9% or more, by weight based on the weight of the SiH crosslinker, while generally being 1.0% or less, and 0.9% or less, 0.8% or less, 0.7% or less, 0.6% or less, 0.5% or less, 0.4% or less, or even 0.3% or less. The content of silicon-bonded hydrogen atoms may be determined by NMR analysis.

[0033] SiH crosslinkers have the unit formula (BI): (R 1 3SiO 1 / 2 )2(R 1 2SiO 2 / 2 ) k (R 1 HSiO 2 / 2 ) m (BI), wherein R 1 is as described above in formula (AI), subscript k≧0, subscript m>0, and the amount (m+k) is 8 to 400. Subscripts m and k indicate that the polyorganohydrogensiloxane crosslinker has a viscosity of 5 to 1,000 millipascals at 25° C. *seconds (mPa·s), a value selected to have a viscosity of 10 to 350 mPa·s at 25°C, or 20 to 100 mPa·s at 25°C. Suitable polyorganohydrogensiloxane crosslinkers can include, for example, trimethylsiloxy terminated poly(dimethylsiloxane / methylhydrogensiloxane), trimethylsiloxy terminated polymethylhydrogensiloxane, or mixtures thereof. The crosslinker can be one polyorganohydrogensiloxane crosslinker or a combination of two or more crosslinkers that can differ in one or more properties selected from molecular weight, structure, siloxane units, and sequence. Suitable commercially available SiH crosslinkers include those available under the designations HMS-071, HMS-301, and DMS-H11, all available from Gelest.

[0034] The relative concentrations of the aliphatically unsaturated polyorganosiloxane (A) and the SiH crosslinker are such that the molar ratio of silicon-bonded hydrogen atoms from the crosslinker to alkenyl groups (e.g., alkenyl groups in the aliphatically unsaturated polyorganosiloxane (A)) in the curable release coating composition (SiH / Vi ratio) ranges from 0.8:1 to 5:1, and can be 0.8:1 or more, 0.9:1 or more, 1.0:1 or more, 1.1:1 or more, 1.2:1 or more, 1.3:1 or more, 1.4:1 or more, 1.5:1 or more, or even 1.6:1 or more, while generally being 5:1, and can be 4:1 or less, 3:1 or less, 2:1 or less, 1.9:1 or less, 1.8:1 or less, 1.7:1 or less, or even 1.6:1 or less.

[0035] Typically, the SiH crosslinker is present in a concentration of 0.1% or greater, and can be 1% or greater, 1.5% or greater, 1.8% or greater, or even 2% or greater, by weight, based on the total weight of the alkenyl group-containing components in the curable release coating composition, while generally being 5% or less, and can be 4% or less, 3% or less, or even 2.5% or less.

[0036] The curable release coating compositions of the present invention include (C) one or more hydrosilylation reaction catalysts. The hydrosilylation reaction catalysts can include platinum group metal catalysts. Such hydrosilylation catalysts may include (C1) metals selected from platinum, rhodium, ruthenium, palladium, osmium, and iridium, preferably platinum; (C2) compounds of such metals, including, for example, chloridetris(triphenylphosphane)rhodium(I) (Wilkinson's catalyst), rhodium diphosphine chelates such as [1,2-bis(diphenylphosphino)ethane]dichlorodirhodium or [1,2-bis(diethylphosphino)ethane]dichlorodirhodium, chloroplatinic acid (Speier's catalyst), chloroplatinic acid hexahydrate, or platinum dichloride; (C3) complexes of metal compounds (C2) with organopolysiloxanes, such as 1,3-diethenyl-1,1,3,3-tetramethyldisiloxane complexes with platinum (Karstedt's catalyst). Hydrosilylation catalysts may be encapsulated (typically in phenyl resins) or non-encapsulated. Exemplary hydrosilylation reaction catalysts are described in US Pat. Nos. 3,159,601 and 3,220,972.

[0037] The amount of hydrosilylation reaction catalyst is used in a catalytic amount, i.e., an amount sufficient to catalyze the hydrosilylation reaction of silicon-bonded hydrogen atoms and alkenyl groups in the curable release coating composition.Typically, the concentration of the hydrosilylation reaction catalyst is 1 parts per million (ppm) or more, 5 ppm or more, 10 ppm or more, 20 ppm or more, or even 30 ppm or more, by weight, based on the weight of the curable release coating composition excluding solvent (if present) (e.g., the total weight of components (A), (B) and (C) above, and (D) below, and optional components (E), (F) and (H) below (if present)), while being sufficient to provide generally no more than 1,000 ppm, no more than 500 ppm, no more than 300 ppm, no more than 130 ppm, or even no more than 100 ppm.

[0038] The curable release coating composition of the present invention comprises (D) particles of a cured organosiloxane composition (also referred to as "cured organosiloxane particles"), optionally with a silica-treated coating. The shape of the particles of the cured organosiloxane composition may be spherical, flat or amorphous. A spherical shape is preferred. The particles of the cured organosiloxane composition may have an average particle size of 0.5 micrometers (μm) or more, and may be 1 μm or more, 2 μm or more, or even 3 μm or more, while generally being 30 μm or less, and may be 25 μm or less, 20 μm or less, 15 μm or less, 14 μm or less, 13 μm or less, 12 μm or less, 10 μm or less, 9 μm or less, 8 μm or less, or even 6 μm or less, as measured using a Malvern Mastersizer Hydro 2000SM (further details are provided below under Particle Size of the Cured Organosiloxane Composition).

[0039] The particles of the cured organosiloxane composition may or may not have a silica-treated coating. Particles with or by a "silica-treated coating" means that the particles have been treated or coated with silica such that the silica particles are present and typically immobilized on the surface of the particles of the cured organosiloxane composition. Desirably, the particles of the cured organosiloxane composition having a silica-treated coating include amorphous silica particles immobilized on the surface of the particles of the cured organosiloxane composition. The amorphous silica particles may have an average particle size of 1 μm or less, 0.5 μm or less, 0.1 μm or less, 0.05 μm or less, 0.02 μm or less, or even 0.01 μm or less, as determined by a Malvern Mastersizer Hydro 2000SM (further details are provided under Particle Size of Amorphous Silica Particles). The amorphous silica particles have an average particle size of 2.0 groups per square nanometer (nm 2 ) or greater, and may exhibit a surface silanol group density of 2.2 groups / nm 2 More than 2.5 units / nm 2 More than 3.0 groups / nm 2 Above, 3.5 units / nm 2 More than 4.0 units / nm2 More than 4.2 groups / nm 2 The silanol group density on the silica surface of the silica-treated coating is calculated from the BET specific surface area, and the silanol group content is calculated from the amount of hydrogen evolved after drying the silica-treated coating at 120°C for 3 hours under a vacuum of at least 2 kilopascals (15 mmHg) and reacting with lithium aluminum hydride. The amorphous silica fine particles are measured to have a surface area of ​​50 square meters per gram (m2) using a Micromeritics Accelerated Surface Area & Porosimetry instrument (ASAP2420) according to ASTM D1993. 2 / g) or more, 2 / g or more, 100m 2 / g or more, 150m 2 / g or even 200m 2 The concentration of the silica-treated coating can be 0 or more, 0.05% or more, 0.1% or more, 0.5% or more, or even 1.0% or more, by weight, based on the total weight of the particles of the cured organosiloxane composition and the silica-treated coating, if present, while generally being 5% or less, 4% or less, 3% or less, or even 1% or less.

[0040] (D) The process of preparing particles of cured organosiloxane composition is known in the art and typically includes (i) preparing an aqueous dispersion of a curable organosiloxane composition, (ii) curing the composition to produce an aqueous dispersion of cured organosiloxane particles, and (iii-1) finally removing water from the aqueous dispersion, preferably by heating. In preparing cured organosiloxane particles with a silica-treated coating, the process may include the above steps (i) and (ii), followed by (iii-2) mixing the aqueous dispersion of cured organosiloxane particles obtained from step (ii) with amorphous silica microparticles or an aqueous dispersion of amorphous silica microparticles, thereby forming an aqueous mixture of cured organosiloxane particles and amorphous silica microparticles, and (iv) subjecting the mixture obtained from step (iii-2) to rubbing consolidation, or heating the mixture obtained from step (iii-2) and then removing water. Heating of the aqueous dispersion or mixture can be carried out at a temperature range of 40-95°C or 60-90°C, which, if present, can immobilize the silica particles on the surface of the cured organosiloxane particles in step (iv) by interaction in water of the silanol groups on the surface of the silica with functional groups such as silanol, silicon-bonded hydrogen, and silicon-bonded alkoxy located on the surface of the cured organosiloxane particles. Examples of cured organosiloxane materials suitable as (D) and their preparation methods are disclosed, for example, in EP 0685508(B1) and EP 0647672(B1).

[0041] One common method for preparing the aqueous dispersion of the curable organosiloxane composition in step (i) above includes dispersing the curable organosiloxane composition in water or an aqueous surfactant solution, and then producing a uniform dispersion therefrom by the action of a suitable device, such as a mixing device such as a homogenizer or colloid mill, or an ultrasonic vibrator. Curable organosiloxane compositions suitable for preparing the cured organosiloxane particles include addition reaction curable organosiloxane compositions, condensation reaction curable organosiloxane compositions, organoperoxide curable organosiloxane compositions, and ultraviolet (UV) curable organosiloxane compositions.

[0042] The materials of the addition reaction curable organosiloxane composition can include (a) an aliphatically unsaturated polyorganosiloxane containing two or more alkenyl groups per molecule, including those described in (A) of the curable release coating composition above, (b) a crosslinker having two or more silicon-bonded hydrogen atoms per molecule, including those described in (B) of the curable release coating composition above, and (c) a hydrosilylation reaction catalyst, preferably a platinum catalyst, including those described in (C) of the curable release coating composition above. The resulting cured organosiloxane particles comprise the reaction product of (a) and (b). Preferably, material (a) in the curable organosiloxane composition comprises one or more linear polydiorganosiloxanes (A-3). Examples of the (a) material include dimethylvinylsiloxy-terminated poly(dimethylsiloxane / methylvinylsiloxane), dimethylvinylsiloxy-terminated polydimethylsiloxane, trimethylsiloxy-terminated poly(dimethylsiloxane / methylvinylsiloxane), dimethylvinylsiloxy-terminated methylsilsesquioxane, vinyl-terminated polydimethylsiloxane, or mixtures thereof. Desirably, the material (b) in the curable organosiloxane composition is selected from trimethylsiloxy-terminated poly(dimethylsiloxane / methylhydrogensiloxane), trimethylsiloxy-terminated polymethylhydrogensiloxane, hydrogen-terminated polydimethylsiloxane, hydrogen-terminated poly(dimethylsiloxane / methylhydrogensiloxane), hydrogen-terminated polymethylhydrogensiloxane, or mixtures thereof. More desirably, the cured organosiloxane particles comprise the reaction product of poly(dimethylsiloxane / methylhydrogensiloxane) with dimethylvinylsiloxy terminated poly(dimethylsiloxane / methylvinylsiloxane), the reaction product of poly(dimethylsiloxane / methylhydrogensiloxane) with dimethylvinylsiloxy terminated methylsilsesquioxane and vinyl terminated dimethylsiloxane, the reaction product of poly(dimethylsiloxane / methylhydrogensiloxane) with dimethylvinylsiloxy terminated poly(dimethylsiloxane / methylvinylsiloxane), or mixtures thereof.

[0043] The curable release coating composition of the present invention may contain (D) particles of a cured organosiloxane composition having an optional silica treated coating, in a concentration by weight based on the weight of the curable release coating composition excluding solvent, if present, of 0.1% or more, and can be 0.15% or more, 0.2% or more, 0.25% or more, 0.3% or more, 0.35% or more, 0.4% or more, 0.45% or more, or even 0.5% or more, while generally being 5% or less, and can be 4.5% or less, 4% or less, 3.5% or less, 3% or less, 2.5% or less, 2% or less, 1.8% or less, 1.5% or less, 1.4% or less, 1.3% or less, 1.2% or less, 1% or less, 0.8% or less, or even 0.5% or less.

[0044] The curable release coating compositions of the present invention may or may not contain (E) one or more hydrosilylation reaction inhibitors (also called "inhibitors"), which are useful for altering the reaction rate of silicon-bonded hydrogen atoms and alkenyl groups in the composition compared to the reaction rate of the same composition but omitting the inhibitor. Examples of suitable inhibitors include acetylenic alcohols such as 2-methyl-3-butyn-2-ol, dimethylhexynol, 3,5-dimethyl-1-hexyn-3-ol, 1-butyn-3-ol, 1-propyn-3-ol, 2-methyl-3-butyn-2-ol, 3-methyl-1-butyn-3-ol, 3-methyl-1-pentyn-3-ol, 3-phenyl-1-butyn-3-ol, 4-ethyl-1-octyne-3-ol, 3,5-dimethyl-1-hexyn-3-ol, and 1-ethynyl-1-cyclohexanol (ETCH); cycloalkenyl siloxanes such as methylvinyl cyclosiloxanes such as 1,3,5,7-tetramethyl-1,3,5,7-tetravinyl cyclotetrasiloxane, and 1,3,5, 7-tetramethyl-1,3,5,7-tetrahexenylcyclotetrasiloxane: enyne compounds such as 3-methyl-3-penten-1-yne, and 3,5-dimethyl-3-hexen-1-yne; triazoles such as benzotriazole; phosphines; mercaptans; hydrazines; amines such as tetramethylethylenediamine, 3-dimethylamino-1-propyne, n-methylpropargylamine, propargylamine, and 1-ethynylcyclohexylamine; fumarates including dialkyl fumarates such as diethyl fumarate, dialkenyl fumarates such as diallyl fumarate, dialkoxyalkyl fumarates; maleates such as diallyl maleate and diethyl maleate; nitriles; ethers; or mixtures thereof.

[0045] Inhibitors useful in the present invention may be present in concentrations of 0 or greater, and may be 0.001% or greater, 0.0025% or greater, or even 0.01% or greater, by weight based on the weight of the release coating composition excluding solvent, if present, while generally being 5% or less, and 1% or less, 0.5% or less, or even 0.25% or less.

[0046] The curable release coating composition of the present invention may or may not include one or more adhesion promoters (F). Suitable adhesion promoters may include, for example, the reaction product of a vinyl alkoxysilane with an epoxy-functional alkoxysilane; the reaction product of a vinyl acetoxysilane with an epoxy-functional alkoxysilane; the blend and / or reaction product of a polyorganosiloxane having at least one aliphatically unsaturated hydrocarbon group and at least one hydrolyzable group per molecule with an epoxy-functional alkoxysilane (e.g., the blend or reaction product of a hydroxy-terminated vinyl-functional polydimethylsiloxane with glycidoxypropyltrimethoxysilane). Examples of suitable epoxy-functional alkoxysilanes include 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, (epoxycyclohexyl)ethyldimethoxysilane, (epoxycyclohexyl)ethyldiethoxysilane, or mixtures thereof. Suitable fixing additives and their preparation methods are disclosed, for example, in U.S. Patent Application Publication Nos. 2003 / 0088042, 2004 / 0254274, and 2005 / 0038188, and European Patent No. 0556023. Suitable commercially available fixing additives can include, for example, SYL-OFF™ 297, SYL-OFF™ 397, and SYL-OFF™ SL9250, all available from Dow Silicones Corporation, Midland, Michigan, USA (SYL-OFF is a trademark of Dow Silicones Corporation).

[0047] The anchoring additives useful in the present invention, when present, may be present in a concentration, by weight based on the weight of the curable release coating composition excluding solvent, of 0 or more, and may be 0.01% or more, 0.05% or more, 0.1% or more, 0.2% or more, 0.3% or more, 0.4% or more, or even 0.5% or more, while generally being 5% or less, and 4% or less, 3% or less, 2% or less, 1.5% or less, or even 1% or less.

[0048] The curable release coating composition of the present invention may or may not include (G) one or more solvents. Suitable solvents may include, for example, polyalkylsiloxanes, alcohols, ketones, aromatic hydrocarbons, aliphatic hydrocarbons, glycol ethers, tetrahydrofuran, mineral spirits, naphtha, tetrahydrofuran, mineral spirits, naphtha, or mixtures thereof. The solvent may include one or more organic solvents including alcohols such as methanol, ethanol, isopropanol, butanol, or n-propanol, ketones such as acetone, methyl ethyl ketone, or methyl isobutyl ketone, aromatic hydrocarbons such as benzene, toluene, or xylene; aliphatic hydrocarbons such as heptane, hexane, or octane; glycol ethers such as propylene glycol methyl ether, dipropylene glycol methyl ether, propylene glycol n-butyl ether, propylene glycol n-propyl ether, or ethylene glycol n-butyl ether, tetrahydrofuran; mineral spirits, naphtha, or combinations thereof. Desirably, the solvent is heptane.

[0049] The solvent may be present in a concentration of 0 or more, 2% or more, 20% or more, or even 50% or more by weight based on the weight of the curable release coating composition, while generally being 99% or less, 50% or less, 20% or less, or even 2% or less. The solvent may be added during the preparation of the release coating composition, for example, to aid in the mixing and delivery of one or more components in the release coating composition described above. For example, the hydrosilylation catalyst may be delivered in a solvent. All or a portion of the solvent may be removed after the preparation of the release coating composition, if desired.

[0050] The curable release coating composition of the present invention may or may not include (H) organically modified functional silica particles having an average particle size of 3 μm to 15 μm as measured using a Malvern Mastersizer Hydro 2000SM according to ASTM D4464-15. The organically modified silica particles may be highly porous silica particles having a porosity of more than 90%. The functional silica particles have one or more organic functional groups on their surface, such as trimethylsilyl, triethylsilyl, dimethylvinylsilyl, and dimethylphenylsilyl. The method for producing component (H) is not limited, and for example, U.S. Patent No. 7,470,725 describes a method comprising a) modifying the surface of a silica aerogel with a silylating agent, and b) drying the surface-modified gel obtained in step a). Such organically modified functional silica particles are commercially available as DOWSIL™ VM-2270 Aerogel Fine Particles from The Dow Chemical Company (DOWSIL is a registered trademark of The Dow Chemical Company). The organically modified functional silica particles may be present at a concentration of 5% or less, 0.5% or less, 0.1% or less, or even 0% by weight of the curable release coating composition excluding solvent (if present). To further improve the transparency of the release coating, it is desirable for the curable release coating composition to be substantially free of organically modified functional silica particles. "Substantially free of organically modified functional silica particles" refers to less than 0.1%, less than 0.05%, less than 0.01%, less than 0.005%, or even 0% by weight based on the weight of the curable release coating composition excluding solvent, if present.

[0051] The curable release coating compositions of the present invention may be prepared by mixing particles of an aliphatically unsaturated polyorganosiloxane (A), a crosslinker (B), a hydrosilylation reaction catalyst (C) and a cured organosiloxane composition (D), and, optionally, a hydrosilylation reaction inhibitor (E), an adhesion promoter (F) and / or a solvent (G). The curable release coating compositions may be prepared as one-part compositions or as multi-part compositions, where the crosslinker and catalyst are stored in separate parts until the parts are combined at the time of use (e.g., immediately prior to application to a substrate).

[0052] The curable release coating composition of the present invention is suitable for use in forming release coatings comprising the cured product of the curable release coating composition, i.e., release coatings formed by curing the curable release coating composition. The release coatings with excellent transparent appearance and anti-blocking properties, as well as desirable low peel force and high sustained adhesive strength, make them suitable for use in electronic device applications, such as release liners for silicone pressure-sensitive adhesives used in electronic device applications, such as touch panels for tape peeling, label peeling and / or adhesive transfer films, especially when transparency is desired. The present invention also relates to a release line comprising a substrate and a release coating formed by curing (e.g., via hydrosilylation reaction) the release coating composition present on at least one surface of the substrate.

[0053] The present invention also relates to a method for preparing a release liner, comprising applying a curable release coating composition to at least one surface of a substrate, such as a film, and curing the curable release coating composition to form a release coating (also referred to as a "cured release coating") on the surface of the substrate, thereby forming a release liner. The release liner comprises a substrate and a release coating on at least one surface of the substrate. The curable release coating composition can be applied to both sides of the substrate. The curable release coating composition can be applied to the substrate by any convenient means, such as spraying, doctor blade, dipping, screen printing, or by a roll coater, such as an offset web coater, kiss coater, etched cylinder coater, or multi-roll coater. The curable release coating composition can be applied to any substrate, typically a sheet-like substrate, including polymeric films, including polyesters, such as polyethylene terephthalate (PET), polyethylene, polypropylene, or polystyrene films; paper substrates, including plastic-coated papers, such as polyethylene, glassine, supercalendered paper, or clay-coated kraft-coated paper; metal foils, such as aluminum foil. Desirably, the substrate can be a PET film. Desirably, the curable release coating composition is applied to at least one surface of a sheet-like substrate using a multiple roll coater.

[0054] The method of preparing a release liner may optionally further comprise treating the surface of the substrate prior to applying the curable release coating composition. Treatment of the substrate may be carried out by any convenient means, such as applying a primer or subjecting the substrate to a corona discharge treatment, etching or plasma treatment prior to coating with the curable release coating composition.

[0055] The method of preparing a release liner may optionally further comprise removing the solvent, if present, before or during curing of the curable release coating composition, which may be done by any conventional means, such as heating at 50°C to 100°C for a time sufficient to remove all or a portion of the solvent. The method of preparing a release liner may further comprise curing the curable release coating composition to form a release coating on the surface of the substrate. Curing may be carried out by any conventional means, such as heating at a temperature depending on the coating line used, typically in the range of 100-240°C, 110-160°C, or 120-150°C, for a time sufficient to cure the release coating composition. For example, curing may be carried out at 120-160°C for off-line coating in an oven, or 200-240°C for in-line coating in an oven. Curing times may be 1 second to 10 seconds, 2 seconds to 20 seconds, or 5 seconds to 30 seconds. The above heating and curing steps can be carried out in an oven, such as an air circulating oven or tunnel furnace, or by passing the coated film around a heated cylinder.

[0056] The coat weight of the release coating is 0.05 grams per square meter (g / m 2 )~2.0g / m 2 The curable release coating composition of the present invention can provide release liners prepared therefrom (i.e., release liners comprising a substrate and a release coating on at least one surface of the substrate) with the following properties: clear appearance (haze value <3.5), anti-blocking properties, low coat weight (e.g., less than 1.3 g / m 2 and / or low peel force (RF-RT<5.0 grams / inch (g / in) or less), high subsequent adhesive strength (SAS>85%). These properties are determined according to the test methods described below in the Examples section.

[0057] The release liner prepared as above can be used to protect the pressure-sensitive adhesive. The user can directly coat the liquid pressure-sensitive adhesive composition on the release liner, remove the solvent or water by heat or UV curing, and then laminate with a substrate and rewind into a roll. Alternatively, the user can laminate the release liner with a dry pressure-sensitive adhesive or adhesive film for tape, label, or die-cutting applications. The present invention also relates to the use of the release liner for silicone pressure-sensitive adhesive articles in electronic device applications. EXAMPLES

[0058] Some embodiments of the present invention will now be described in the following examples, where weight percent (wt%) values ​​are by weight of the composition unless otherwise specified. Table 1 lists materials for use in the sample release coating compositions described herein below. Note: "Vi" stands for vinyl and "Me" stands for methyl.

[0059] [Table 1] * The particle size of the Epowder was determined using a Malvern Mastersizer Hydro 2000 SM (further details are provided below under Particle Size of the Cured Organosiloxane Compositions).

[0060] IE1~10 and CE A~H samples The formulations for the release coating composition samples are in Table 2, with the amounts of each component reported in grams (g) unless otherwise indicated.

[0061] The samples were prepared by mixing the components together using a SpeedMixer™ DAC 400 FVZ mixer from FlackTek Inc. (South Carolina, USA). Add Vi polymer, Epowder or silica particles, adhesion promoter, SiH crosslinker and inhibitor to the cup of the SpeedMixer. Mix at 3,000 revolutions per minute (RPM) for 30 seconds several times until homogenous. Add an appropriate amount of heptane solvent as needed to reach the target coat weight (CW) shown in Table 2. Catalyst was added and the resulting mixture was mixed for 10 minutes to form the release coating composition.

[0062] The release coating compositions were then coated onto a PET film substrate (thickness: 50 μm) using a coater and cured by thermal addition curing in an oven at 140° C. for 30 seconds, thereby forming a release liner including a cured release coating on the substrate. Three samples of each release coating composition were prepared and evaluated according to the test methods described below, and the results were averaged.

[0063] Coat Weight (CW) Coat weight (g / m2) was measured using X-rays to detect the coat weight of the cured release coating on the PET film substrate using an Oxford lab-x 3500 instrument manufactured by Oxford Instruments PLC (Oxon, United Kingdom). 2 ) was evaluated. Uncoated PET was used as a control sample (blank). The test method was based on FINAT Test Method No. 7 (FINAT Technical Handbook 7 th edition, 2005).

[0064] Peel Force - Room Temperature ("RF-RT") RF-RT in g / in (0.386 centinewtons / centimeter) was evaluated using a 180 degree peel test to measure the peel force from a release liner. Tesa 7475 standard tape was laminated onto the cured release coating and tested at 20 g / cm2 A loading of 1000 g was placed on the resulting laminated sample and allowed to sit at room temperature (25° C. room temperature) for 20 hours. After 20 hours, the loading weight was removed and the sample was allowed to sit for 30 minutes. The peel force ("RF-RT") was then tested by a ChemInstruments AR-1500 using FINAT Test Method No. 10 (FINAT Technical Handbook 7th edition, 2005).

[0065] Peel force - Aging ("RF-70℃ Aging") RF-70°C aging was evaluated by measuring the release force from the release liner using a 180° peel test. Tesa 7475 standard tape was laminated onto the cured release coating and the resulting laminated sample was applied with 20 g / cm 2 A loading weight of 100 g was applied and the sample was left at 70° C. for 20 hours. After 20 hours, the loading weight was removed and the sample was left for 30 minutes. The peel force ("RF-70° C. Aging") was then measured according to FINAT Test Method No. 10 (FINAT Technical Handbook 7 th The tests were performed using a ChemInstruments AR-1500 using the Chromatographic Method (Chem. 2005 edition).

[0066] SAS (Subsequent Adhesion Strength, an index of migration) The SAS in percent was evaluated as follows: The test tapes were applied to the cured release coating at 20 g / cm with Nitto Denko 31B tape. 2 The samples were laminated with a loading weight of 1000g and left at 70°C for 20 hours. After 20 hours, the loading weight was removed and the samples were left at room temperature for 30 minutes. The 31B tape was then transferred onto the PET substrate and left for an additional hour. The peel force ("RF(peel)") was measured according to FINAT Test Method No. 11 (FINAT Technical Handbook 7 thThe SAS test was performed on a ChemInstruments AR-1500 using the 2005 edition. In this SAS test, Laminate 31B tape on a polytetrafluoroethylene (PTFE) substrate was tested, and the PTFE sample was then processed and evaluated in the same manner as the cured release coating sample above, and the release force ("RF(PTFE)") was recorded. The SAS value was recorded as RF(Release) / RF(PTFE) x 100%.

[0067] Anti-blocking test A 25 millimeter (mm) x 150 mm uncoated PET film was laminated with the same size release liner prepared above by rolling twice in each direction with a standard FINAT test roller at a speed of approximately 10 mm per second to obtain intimate contact between the release liner and the surface of the PET film. Observe by visual inspection to determine if there is any visible "wetting" at the interface of the PET film and the release liner. The sample passes if there is no visible wetting and is reported as a "P". Otherwise, the sample fails if there is visible wetting and is reported as an "F".

[0068] Hayes The haze of the above prepared release liners was tested by BYK Gardner Haze Gard Plus according to ASTM D1003.

[0069] transparency The clarity of the above prepared release liners was assessed by visual inspection and reported as "clear" and "hazy."

[0070] Particle size of the cured organosiloxane composition One gram of the cured organosiloxane composition particles and 100 milliliters (mL) of ethanol were charged into a 300 mL plastic cup and mixed with a disperser for 30 seconds. The resulting mixture was ultrasonically mixed for 3 minutes and the particle size was measured in water using a Malvern Mastersizer Hydro 2000SM.

[0071] Particle size of amorphous silica particles 1 g of amorphous silica microparticles and 100 mL of ethanol were placed in a 300 mL plastic cup and mixed for 30 seconds with a disperser. The resulting mixture was ultrasonically mixed for 3 minutes and the particle size was measured in water using a Malvern Mastersizer Hydro 2000SM.

[0072] The characterization results of the release coating composition samples are shown in Table 2.

[0073] As shown in Table 2, samples IE1-10 achieved a transparent appearance (e.g., haze value less than 3.5) and low peel force with anti-blocking properties to the backside of the film (RF-RT<5.0 g / in) while maintaining comparable SAS and RF-70°C aging properties tested under the same conditions compared to samples CE A-H. In contrast, samples CE A-H shown in Table 2 failed to achieve at least one of the transparency and anti-blocking requirements.

[0074] [Table 2] NOTE: "SiH / Vi ratio" refers to the molar ratio of SiH functionality to vinyl functionality from the crosslinker. * The solvent used for each sample (heptane) was added in an amount appropriate to reach the target coat weight (CW) shown in Table 2.

Claims

1. 1. A curable release coating composition comprising: (A) an aliphatic unsaturated polyorganosiloxane having two or more alkenyl groups per molecule; (B) a crosslinker having two or more silicon-bonded hydrogen atoms per molecule in an amount sufficient to provide a molar ratio of silicon-bonded hydrogen atoms to alkenyl groups in said curable release coating composition of from 0.8:1 to 5:1; (C) a catalytic amount of a hydrosilylation reaction catalyst; (D) 0.01% to 5% by weight, based on the weight of the curable release coating composition excluding solvent, if present, of particles of the cured organosiloxane composition, optionally having a silica treated coating, having an average particle size of 0.5 to 30 micrometers; 1. A curable release coating composition comprising:

2. 10. The release coating composition of claim 1, further comprising a hydrosilylation reaction inhibitor, an adhesion promoter, a solvent, or a mixture thereof.

3. 3. The release coating composition of claim 1 or 2, wherein the particles of the cured organosiloxane composition comprise the reaction product of (a) an aliphatically unsaturated polyorganosiloxane containing two or more alkenyl groups per molecule, and (b) a crosslinker having two or more silicon-bonded hydrogen atoms per molecule, wherein (a) is selected from dimethylvinylsiloxy-terminated poly(dimethylsiloxane / methylvinylsiloxane), dimethylvinylsiloxy-terminated polydimethylsiloxane, trimethylsiloxy-terminated poly(dimethylsiloxane / methylvinylsiloxane), dimethylvinylsiloxy-terminated methylsilsesquioxane, vinyl-terminated polydimethylsiloxane, or mixtures thereof.

4. 4. The release coating composition of any one of claims 1 to 3, comprising from 0.1% to 2% by weight of particles of said cured organosiloxane composition, based on the weight of the curable release coating composition excluding solvent, if present.

5. The release coating composition of any one of claims 1 to 4, wherein the aliphatically unsaturated polyorganosiloxane is selected from a Q branched polyorganosiloxane, a silsesquioxane, a linear polyorganosiloxane, or a combination thereof.

6. The Q-branched polyorganosiloxane has the unit formula (AI): (R 1 3 SiO 1/2 ) a (R 2 R 1 2 SiO 1/2 ) b (R 1 2 SiO 2/2 ) c (R 2 R 1 SiO 2/2 ) c’ (SiO 4/2 ) d (A-I) wherein each R 1 are independently a monovalent hydrocarbon group free of aliphatic unsaturation or a monovalent halogenated hydrocarbon group free of aliphatic unsaturation, and each R 2 are independently an alkenyl group, with subscript a > 0, subscript b > 0, 995 > c + c' > 15, and subscript d > 0; The silsesquioxane has the unit formula (A-II): (R 1 3 SiO 1/2 ) e (R 2 R 1 2 SiO 1/2 ) f (R 1 2 SiO 2/2 ) g (R 1 SiO 3/2 ) h (A-II) wherein each R 1 are independently a monovalent hydrocarbon group free of aliphatic unsaturation or a monovalent halogenated hydrocarbon group free of aliphatic unsaturation, and each R 2 are independently an alkenyl group, subscript e≧0, subscript f>0, subscript g is 15 to 995, and subscript h>0; The linear polydiorganosiloxane is (A-III-1), (A-III-2), or a combination thereof: (R 1 2 R 2 SiO 1/2 ) 2 (R 1 2 SiO) n (R 1 R 2 SiO) o (A-III-1) (R 1 3 Yes 1/2 ) 2 (R 1 2 Yes) p (R 1 R 2 Yes) q (A-III-2) wherein each R 1 are independently a monovalent hydrocarbon group free of aliphatic unsaturation or a monovalent halogenated hydrocarbon group free of aliphatic unsaturation, and each R 2 are independently an alkenyl group; subscript n is from 5 to 10,000; subscript o has a value sufficient to provide an alkenyl content of from 0.01% to 5.0% by weight, based on the weight of said polydiorganosiloxane of unit formula (A-III-1); subscript p is from 5 to 10,000; and subscript q is sufficient to provide an alkenyl content of from 0.01% to 5.0% by weight, based on the weight of the polydiorganosiloxane of unit formula (A-III-2); The release coating composition of claim 5.

7. The crosslinking agent is represented by the unit formula (BI): (R 1 3 SiO 1/2 ) 2 (R 1 2 SiO 2/2 ) k (R 1 HSiO 2/2 ) m (B-I) wherein each R 1 are independently a monovalent hydrocarbon group free of aliphatic unsaturation or a monovalent halogenated hydrocarbon group free of aliphatic unsaturation, subscript k≧0, subscript m>0, and the amount (m+k) is 8 to 400; The release coating composition of any one of claims 1 to 6.

8. 8. The release coating composition of any one of claims 1 to 7, wherein the hydrosilylation reaction catalyst is present in an amount sufficient to provide from 1 ppm to 1000 ppm by weight of platinum group metal, based on the weight of the curable release coating composition excluding solvent, if present.

9. 9. The release coating composition of claim 1, wherein the particles of the cured organosiloxane composition having the silica-treated coating comprise amorphous silica microparticles immobilized on the surface of the particles of the cured organosiloxane composition.

10. 1. A method for preparing a release liner comprising a release coating on at least one surface of a substrate, comprising: Optionally, treating at least one surface of said substrate; 1) applying to the surface of the substrate a curable release coating composition according to any one of claims 1 to 9; Optionally, 2) removing the solvent, if present; 3) curing the composition to form a release coating on the surface of the substrate; and A method comprising:

11. 10. A release liner comprising a substrate and a release coating present on at least one surface of the substrate, the release coating being formed by curing the curable release coating composition of any one of claims 1 to 9.

12. 12. The release liner of claim 11 having a haze value of less than 3.5 as measured according to ASTM D1003.

Citation Information

Patent Citations

  • Silicone composition for releasing use

    JP1990298550A

  • Coating composition and its uses

    WO2020233268A1

  • Composition for preparing a release coating

    WO2021113058A1